Emotional and Clinical Aspects Observed in Women with Gestational Trophoblastic Disease: A Multidisciplinary Action - França, Ana Carolina Gomes; Uberti, Elza Maria Hartmann; Muller, Karine Paiva; Cardoso, Rodrigo Bernardes; Giguer, Fabiana; El Beitune, Patricia; Braga, Antonio (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To evaluate the emotional and clinical aspects observed in women with gestational trophoblastic disease (GTD) followed-up in a reference center (RC) by a multidisciplinary team.Methods Retrospective cohort study of the clinical records of 186 women with GTD and of the emotional aspects (EA) observed in these women by a team of psychologists and reported by the 389 support groups conducted from 2014 to 2018.Results The women were young (mean age: 31.2 years), 47% had no living child, 60% had planned the pregnancy, and 50% participated in two or more SG. Most women (n = 137; 73.6%) reached spontaneous remission of molar gestation in a median time of 10 weeks and had a total follow-up time of seven months. In the group of 49 women (26.3%) who progressed to gestational trophoblastic neoplasia (GTN), time to remission after chemotherapy was 18 weeks, and total follow-up time was 36 months. EA included different levels of anxiety and depression, more evident in 9.1% of the women; these symptoms tended to occur more frequently in women older than 40 years (p = 0.067), less educated (p = 0.054), and whose disease progressed to GTN (p = 0.018), as well as in those who had to undergo multi-agent chemotherapy (p = 0.028) or hysterectomy (p = 0.001) adjuvant to clinical treatment.Conclusion This study found several EA in association with all types of GTD. It also highlights the importance of specialized care only found in a RC, essential to support the recovery of the mental health of these women.
Keywords: gestational trophoblastic disease; psychological aspects; support group; mental health